Micromagnetic Study of Synchronization of Nonlinear Spin-Torque Oscillators to Microwave Current and Field - M. Carpentieri; G. Finocchio; A. Giordano; B. Azzerboni; F. Lattarulo (Advances in Condensed Matter Physics)
The nonautonomous dynamics of spin-torque oscillators in presence of both microwave current and field has been numerically studied in nanostructured devices. When both microwave current and field are applied at the same frequency, integer phase locking at different locking ratio is found. In the locking region, a study of the intrinsic phase shift between the locking force (current or field) and the giant magnetoresistive signal as a function of the bias current is also exploited.